Desenvolvimento e avaliação de uma proteína quimérica recombinante para o diagnóstico e prognóstico das leishmanioses tegumentar e visceral - Nathalia Coral Galvani (2023)
Leishmaniasis are neglected tropical diseases with high endemicity that affect thousands of people in the world. Infection is caused by protozoan parasites of the genus Leishmania. The biological diversity between species is what allows determining the clinical manifestations, either in the form of visceral leishmaniasis (VL) or tegumentary leishmaniasis (TL). Among these clinical manifestations, VL is considered the most serious, due to its high lethality and great emergence in individuals with infection caused by the human immunodeficiency virus (HIV). Currently, the control and prevention measures adopted by the World Health Organiza-tion (WHO) are based on a combination of intervention strategies against the infection, since an effective and early diagnosis is essential to intervene with the appropriate treatment, decrea-sing mortality rates and evolution of clinical complications. However, the serological tests used show impaired sensitivity and specificity in patients with leishmaniasis and/or coinfected with VL/HIV, due to low levels of anti-leishmanial antibodies or the presence of diseases that cause cross-reaction, leading to false-positive results. The sensitivity also becomes variable in treated patients, since the serology can remain positive for months or years after the end of the trea-tment and cure of the disease. Seeking to solve this problem, the identification of new antigens, through bioinformatic analysis associated with immunoproteomic, has allowed the detection of new proteins with potential diagnostic application. In previous studies, the hypothetical proteins LiHyT, LiHyD, LiHyV and LiHyP were found in species of Leishmania spp, and evaluated in their recombinant versions through ELISA assays, and satisfactory results were obtained for the detection of human and canine VL. Based on this information, the present work aimed to develop a recombinant chimera protein through on the prediction of specific linear epitopes of B cells derived from these four antigenic proteins of L. infantum and to evaluate its diagnostic potential, as well as the individual peptides that constitute it, against human leishmaniasis, as well as co-infection with HIV, in addition to testing them as possible prognostic markers of patients after VL and TL treatment. The amino acid sequences of the proteins were evaluated and eight B cell epitopes were predicted and used in the construction of a new chimeric protein. The protein was expressed, purified and evaluated as a recombinant antigen in ELISA for the diagnosis of VL, TL, VL/HIV co-infection and prognosis in samples from patients treated for VL and TL. The B cell epitopes used in the construction of the chimera were synthesized and also tested in ELISA against the same samples, as well as a soluble Leishmania braziliensis antigenic extract (SLA). The results showed that the chimera protein apresented sensitivity and specificity of 100% for diagnosing VL, TL and VL/HIV, while the synthetic peptides showed sensitivity ranging from 9.1% to 90.9% for TL samples and 76.8 % to 99.2% for VL and VL/HIV samples, while the specificity values reached from 98.3% to 99.1% for TL and 67.1% to 95.7% for VL and VL/HIV. The SLA showed sensitivity and specificity of 18.2% and 98.3% for TL, and 56.8% to 69.5% for VL and VL/HIV samples, respectively. A preliminary prog-nostic evaluation also showed that anti-chimera antibodies significantly decreased when com-pared to serological reactivity before and six months after treatment, suggesting a possible prognostic role of the antigen for leishmaniasis. The present study proved to be effective in the construction and evaluation of new candidates, who demonstrate good performance in diagnos-tic and prognostic detection for leishmaniasis and VL/HIV co-infection.